Long term effects of soluble endoglin and mild hypercholesterolemia in mice hearts - Vitverova, Barbora; Najmanova, Iveta; Vicen, Matej; Tripska, Katarina; Sa, Ivone Cristina Igreja; Hyspler, Radek; Pericacho, Miguel; Nachtigal, Petr (PLOS ONE, 2020)
Soluble endoglin (sEng) released into the circulation was suggested to be related to cardiovascular based pathologies. It was demonstrated that a combination of high sEng levels and long-term exposure (six months) to high fat diet (HFD) resulted in aggravation of endothelial dysfunction in the aorta. Thus, in this study, we hypothesized that a similar experimental design would affect the heart morphology, TGFβ signaling, inflammation, fibrosis, oxidative stress and eNOS signaling in myocardium in transgenic mice overexpressing human sEng. Three-month-old female transgenic mice overexpressing human sEng in plasma (Sol-Eng+ high) and their age-matched littermates with low levels of human sEng (Sol-Eng+ low) were fed a high-fat diet containing 1.25% of cholesterol and 40% of fat for six months. A blood analysis was performed, and the heart samples were analyzed by qRT-PCR and Western blot. The results of this study showed no effects of sEng and HFD on myocardial morphology/hypertrophy/fibrosis. However, the expression of pSmad2/3 and p-eNOS was reduced in Sol-Eng+ high mice. On the other hand, sEng and HFD did not significantly affect the expression of selected members of TGFβ signaling (membrane endoglin, TGFβRII, ALK-5, ALK-1, Id-1, PAI-1), inflammation (VCAM-1, ICAM-1), oxidative stress (NQO1, HO-1) and heart remodeling (PDGFβ, COL1A1, β-MHC). In conclusion, the results of this study confirmed that sEng, even combined with a high-fat diet inducing hypercholesterolemia administered for six months, does not affect the structure of the heart with respect to hypertrophy, fibrosis, inflammation and oxidative stress. Interestingly, pSmad2/3/p-eNOS signaling was reduced in both the heart in this study and the aorta in the previous study, suggesting a possible alteration of NO metabolism caused by six months exposure to high sEng levels and HFD. Thus, we might conclude that sEng combined with a high-fat diet might be related to the alteration of NO production due to altered pSmad2/3/p-eNOS signaling in the heart and aorta.